A Practical Synthesis of Homoallylic Diene Halides: Versatile Synthons for the Preparation of the Taxane A-Ring System - Espinoza-Hicks, José C.; Zaragoza-Galán, Gerardo; Camacho-Dávila, Alejandro A. (Synthesis, 2023)
A concise and efficient synthesis of two homoallylic halides, which are useful precursors for the preparation of the taxane A-ring system is reported. Contrary to the synthetic routes reported in the literature, this procedure does not employ expensive tetramethylethylene as a starting material. The synthetic route uses readily available and inexpensive ethyl acetoacetate, 1,2-dibromoethane, methyltriphenylphosphonium iodide and methylmagnesium bromide as starting materials. The key step in the synthesis is the acid-mediated ring opening of a cyclopropyl tertiary alcohol to afford the corresponding homoallylic diene halides. The corresponding Grignard reagent, derived from the bromide, is used in the synthesis of an enone previously used as a precursor of taxadienone by reaction with the enol ethyl ether of 1,3-cyclohexanedione.
Keywords: taxanes; diene; cyclopropyl alcohol; Diels–Alder